Determining the radiometric response function from a single grayscale image - Lin, Steve; Zhang, L. (IEEE Conference on Computer Vision and Pattern Recognition (CVPR), 2005)
A method is presented for computing the radiometric response function of a camera from a single grayscale image. While most previous techniques require a set of registered images with different exposures to obtain response data, our approach capitalizes on a statistical feature of graylevel histograms at edge regions to gain information for radiometric calibration. Appropriate edge regions are automatically determined by our technique, and a prior model of radiometric response functions is employed to deal with incomplete data. With this single-image method, radiometric calibration becomes possible to perform in many instances where the camera is unknown.